Protonated Ethylene Carbonate: A Highly Resonance‐Stabilized Cation. Issue 12 (25th November 2021) - Beck, Stefanie; Jessen, Christoph; Kornath, Andreas J.
Abstract: Invited for this month's cover picture is the group of Prof. Andreas J. Kornath at the LMU in Munich (Germany). The cover picture shows the crystal structure of the salt of protonated ethylene carbonate [C3 H5 O3 ][Sb2 F11 ]. Protonated ethylene carbonate was synthesized by reacting the neutral compound in the superacidic system HF/SbF5 at low temperature. Interestingly, the single‐crystal X‐ray structure analysis revealed a planar CO3 moiety with nearly equal CO bond lengths. Further theoretical investigations of the cation led to the result, that it contains a remarkably delocalized 6π‐electron system. On the cover this resonance stabilization is highlighted by p‐orbitals on the CO3 moiety. Read the full text of their Research Article at 10.1002/open.202100229 . Abstract : " …we were able to prepare a new compound with a highly remarkably delocalized 6π‐electron system…" Find out more about the story behind the front cover research at 10.1002/open.202100229 .